A conceptual study on supply chain management in creating customer value - Rahman, Muhammad Sabbir; Anwar, Md. Aftab; Azam, Ferdous; Abdelfattah, Fadi Abdelmuniem (Academic Research Publishing Group, 2015)
The aim of this conceptual paper is to explicate the impact of effective supply chain management in creating customers’ value. This study applied secondary source to collect all the relevant information in order to derive the conceptual framework. The findings suggest that effective supply chain management has a positive impact on the sustainability, organizational performance, competitiveness and innovativeness in way to creating ultimate value for the customers.